Autonomic Neuropathy in Healthy Elderly Person - Islam, Taslima; Begum, Noorzahan; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2014)
Background: Cardiac autonomic nerve function can be affected in older age. Objective: To find out the degree of autonomic neuropathy by autonomic nerve function scoring system in apparently healthy elderly subjects. Methods: This cross sectional study was conducted in the Department of Physiology, BSMMU, Dhaka between July 2005 and June 2006.For study group, 30 elderly subjects age ranged from 51-60 years were enrolled in one group whereas another 30 elderly subjects age between 61-70 years were enrolled in another group. For comparison sex and BMI matched thirty apparently healthy adults with age from 21-30 years were studied as control. Autonomic nerve function status of all the subjects were examined by five simple non-invasive cardiovascular reflex tests Valsalva maneuver deep breathing test, orthostatic test handgrip test, and sudden standing. Autonomic nerve function (ANF) scoring was done to find out the degree of autonomic neuropathy. Results: 23.34% of subjects of 61-70 years group showed autonomic nerve dysfunctions and 20% had early involvement and 3.34% of them had definite involvement of Autonomic neuropathy. But this percentage was relatively less (10%) in 51-60 years who had early involvement and none had found definite involvement whereas autonomic nerve function was normal in 21-30 years age group.. Conclusion: From this study, it can be concluded that aging process substantially impaired cardiovascular autonomic nerve function. DOI: http://dx.doi.org/10.3329/jbsp.v8i2.18658 Bangladesh Soc Physiol. 2013, December; 8(2): 77-83